PEMBENTUKAN KEAHLIAN KEJURUAN DI INDUSTRI PERALATAN - Padang Wicaksono; Lionel Priyadi; Oscar Vitriano (Program Pendidikan Vokasi Universitas Indonesia, 2014)
Abstract - After 1998 financial crisis, the growth of Indonesian manufactures sector had been dominated bythe technology intensive- tools and machinery sub sector. The development of tools and machinery sub-sectorshould have increased the demand for skilled and specific labors namely vocational high school (VHS)graduates. Nevertheless, the VHS graduates’ roles had relatively been reduced. Despite they have betteropportunities to develop their career in the long term, they are less likely to achieve supervisory or higher careerlevel because the diploma or undergraduates workers most likely occupy the level. One of the main factorsbehind their lower career level prospects is due to rare opportunities to upgrade their skills through further Onthe Job Training in the shop floor. Coincidently, this arguably happened due to the declining position ofIndonesian tools and machinery industry within global value chain from previously export oriented to domesticmarket oriented. Therefore, the existing technology transfer relatively hardly needs sophisticated skills whichconsequently could be delivered by less skilled workers such as general high school (GHS) graduates.